Uterine anteversion after uterine fibroid embolization - Raissi, Driss (Radiol Case Rep, 2018)
Uterine fibroid embolization has been proven effective in treating symptomatic uterine fibroids for appropriately selected patients as an alternative option to surgical approaches. The most common adult uterine position is anteverted followed by a retroverted uterus which can be found in roughly 15%-20% of normal adult females. The positioning of the uterus can change from anteversion to retroversion due to the filling of bladder or during pregnancy; however, changing from retroverted to anteverted position without prior pregnancy or endometriosis is rather uncommon. Here, we describe a case of uterine orientation change from retroversion to anteversion presenting 6 months after uterine fibroid embolization.